Flow and transport in fractured porous media - Dietrich P; Helmig R; Hotzl H; Kongeter J; Sauter M; Teutsch G (Berlin Springer-Verlag, 2005)
This book addresses the characterization of flow and transport in fractured porous media from experimental and modeling perspectives. The volume explores porous media problems, from the distribution of the fractured porous aquifers to their characterizat
Keywords: Applied fluid dynamics; Flow(Fluid dynamics); Porous media